Analysis of failure associated with longwall face during the main weighting period using a numerical modelling approach. Issue 4 (2nd October 2022) - Murmu, Sunny; Budi, Gnananandh
ABSTRACT: A FLAC 3D based model has been developed to estimate the extent of coal wall spalling for a longwall face having a working depth of 406.5 m during the main weighting period. The results obtained from the model helped in characterizing two key phases of main weighting, namely, peak stress, and main fall period based on vertical stress concentration factor, percentage of yield zones, and extent of yielding ahead of the face. The maximum extent of coal wall spalling of 2 m was observed during the main fall period. Spalling is mainly concentrated near the upper-middle and the top sections of the face.